Myhre Syndrome Associated With Dunbar Syndrome and Urinary Tract Abnormalities: A Case Report - Varenyiova, Zofia; Hrckova, Gabriela; Ilencikova, Denisa; Podracka, Ludmila (Frontiers in Pediatrics, 2020)
Myhre syndrome is a rare condition caused by a mutation in the SMAD4 gene, which leads to a defective TGF-β/BMP signalling, resulting in the proliferation of abnormal fibrous tissues. Clinically, patients with Myhre syndrome manifest with defects of connective tissue (skin, muscles, joints), and cardiovascular and neurological impairment. In our report, we present a case of a 16-year-old female with skeletal abnormalities, reduced articular mobility, skin and muscular hypertrophy and cardiovascular defects characteristic of Myhre syndrome. Long-term pulmonary hypertension and arterial hypertension were persistent in spite of antihypertensive treatment. Our patient was also diagnosed with chronic kidney disease and Dunbar syndrome, which is an external compression of the coeliac trunk or coeliac artery by the surrounding tissues. Until now, only a few cases of renal complications in Myhre syndrome have been published. We describe for the first time a female patient with genetically confirmed Myhre syndrome caused by the p.Ile500Val SMAD4 mutation presenting with an unusual occurrence of congenital vesicoureteral reflux, proteinuria with a decreased renal function, and a condition recognized as Dunbar syndrome.